Assay of the individual components of the trivalent oral polio vaccines. - Bagoyo, Remedios C. (1983)
Some of the trivalent oral poliovaccines (OPV) used in the Expanded Program on Immunization in the Philippines in the 1st round, January of 1982, were assayed for the individual poliovirus components' concentration. The results were assessed according to the standards set by the World Health Organization. A total of 29 trivalent OPVs were assayed. 3 were predistribution samples and 26 samples were returned from RHOs and PHOs within the prescribed period only (April to May, 1982) of which 10 were RHO samples and 16 were PHO samples. The procedure of assays followed essentially the methodology recommended by WHO(67). It consists of neutralization test using Vero cells and adapted to the microtiter technique. The results indicate that by and large the trivalent OPVs did not comply with the standards set by the WHO, that is a trivalent OPV should contain 10(exponent of 6) TCD50 per dose of poliovirus type I, 10(exponent of 5) TCD50 per dose of poliovirus type II, and 10(exponent of 5.5) TCD50 per dose of poliovirus type III. Considering individual virus components, 3.4 (1/29) complied for poliovirus type I, none complied for poliovirus type II, and 37.9 (11/29) complied for poliovirus type III. Because of the limited number of samples, inferences are only true for the vaccines which have been represented. It is therefore expected that vaccinees immunized with these vaccines will not produce the level of immunity that is adequate for protection against an infection against the polioviruses. Statistical analysis of the titers of each type of poliovirus among the predistribution, RHO and PHO OPV samples indicate that there are no significant differences among the predistribution and PHO or RHO samples ( = 0.1). It could be inferred from the findings that the cold chain system was efficient and that proper handling of vaccines in the field was observed.
Thesis (Master of Science in Public Health)--University of the Philippines Manila.
Keywords: Oral polio vaccines